Mapping information regarding the work-related disability of depression and long-term musculoskeletal pain to the International Classification of Functioning, Disability and Health and ICF Core Sets - Fresk, Magdalena; Grooten, Wilhelmus J. A; Brodin, Nina; Backlund, Lars G.; Arrelöv, Britt; Skånér, Ylva; Kiessling, Anna (Frontiers in Rehabilitation Sciences, 2023)
Introduction The International Classification of Functioning, Disability and Health is the WHO coding scheme for functioning-related data. Clear and unambiguous information regarding patients' work-related disabilities is important not only for the assessment of entitlement to paid sickness benefits but also for planning rehabilitation and return to work. The objective was to validate the content of ICF and ICF Core Sets for information on work-related disability in sick leave due to depression and long-term musculoskeletal pain. Specific aims: To describe to what extent (1) such data could be linked to ICF and (2) the result of the ICF linking in terms of ICF categories was represented in relevant ICF Core Sets. Methods An ICF-linking study following the ICF-linking rules. A random sample of sick leave certificates issued in primary care for either depression (n = 25) or long-term musculoskeletal pain (n = 34) was collected from a community with 55,000 inhabitants in Stockholm County, Sweden. Results The results of the ICF linking consisted of codings for (1) ICF categories and (2) other health information not possible to link to ICF. The ICF categories were compared to ICF Core Sets for coverage. The majority of the meaning units, 83% for depression and 75% for long-term musculoskeletal pain, were linked to ICF categories. The Comprehensive ICF Core Set for depression covered 14/16 (88%) of the ICF categories derived from the ICF linking. The corresponding figures were lower for both the Brief ICF Core Set for depression 7/16 (44%) and ICF Core Set for disability evaluation in social security 12/20 (60%). Conclusion The results indicates that ICF is a feasible code scheme for categorising information on work-related disability in sick leave certificates for depression and long-term musculoskeletal pain. As expected, the Comprehensive ICF Core Set for depression covered the ICF categories derived from the certificates for depression to a high degree. However, the results indicate that (1) sleep- and memory functions should be added to the Brief ICF Core Set for depression, and (2) energy-, attention- and sleep functions should be added to the ICF Core Set for disability evaluation in social security when used in this context.